METHODOLOGICAL PRINCIPLES AND SPECIFICS OF MANAGEMENT OF SYSTEMIC DEVELOPMENT OF HEALTHCARE INSTITUTIONS - STAHIV, OLEG (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to substantiate the theoretical and methodological foundations of the study, to determine the specifics, as well as to build a system of management elements for the systemic development of health care facilities.The urgency of the problem of development of theoretical and methodological bases of research of management of system development of health care institutions is revealed. Scientific approaches to the essential interpretation of development management at the micro level are generalized.The specifics and features of the management of systemic development of health care enterprises are identified. The system of principles of management of systemic development of health care institutions is identified and their essential and content characteristics are revealed. The structural elements and the algorithm of management of system development of the enterprise which specialize in rendering of services in the field of public health services are defined. The semantic characteristics of such elements as economic interests of business management entities (owners, investors, founders, managers, personnel, external contractors, consumers), principles, functions, methods, strategy and tactics, management mechanisms and tools, management objects, implemented measures, and their results.The applied significance of the research results is to build a system (and its structure) of elements that together provide management of systemic development of health care facilities.The scientific novelty of the research results is the identification of such specific features of the management of systemic development of health care enterprises as principles (emphasis on the formation of a management culture focused on quality satisfaction of medical and diagnostic needs of clients (human-centeredness), focus of management actions on increasing quantitative and improving the structural and qualitative results of medical and diagnostic services (synergy), parity attention to the implementation of the policy of external social responsibility, including the education of a healthy society (external social responsibility), methods (traditionally, administrative management methods are preferred, while as the health care system is reformed, the role of economic and socio-psychological) and tools (mechanisms and tools for management and decision-making should be based on modern information technologies through the automation of medical records and medical information management; transformation of classical management mechanisms towards market on the basis of development of contractual relations (health care institution - client; state - health care institution)) for development.
Keywords: health care; medical services; enterprises; system development; controls